Practice and barriers of technology integrated pedagogy in teaching EFL young learners: A critical analysis - Faudi, Faudi; Husain, Balqis; Musthafa, Bachrudin (Journal of Research in Instructional, 2023)
Young learners' characteristics, which differ from those of young adolescents, adolescents, and adults, encourage EFL instructors to implement technology-based learning strategies with high consideration. If EFL teachers fail to implement the appropriate strategy for teaching English, young students may likely encounter academic difficulties in subsequent years. Teachers of English as a foreign language (EFL) have implemented technology-based learning strategies to improve students' literacy, vocabulary, and critical thinking abilities. There are also implementation obstacles. This article aims to identify the types of digital-based learning strategies implemented by Indonesian EFL teachers for teaching English to young learners, as well as to identify the challenges faced by Indonesian EFL teachers when implementing digital-based learning strategies for young learners.The findings indicated that EFL teachers in Indonesia employed a variety of technological approaches to develop their students' language and critical thinking skills. EFL teachers utilized multimodal e-books to improve reading skills; animated e-books were employed to enhance literacy skills; flipped classroom was utilized to augment vocabulary; and digital folklore was used to foster analytical and critical thinking skills among EFL young learners.